THE ORIGIN OF THE ATHLETICS SPORTS TOUR - Z.B.Khamraeva (Journals Park Publishing, 2022)
This article provides information about the history, development, place of athletics in the Olympic Games, the role of athletics in the physical education of young people.
Keywords: athletics; running; jumping